A gut microbiome signature for HIV and metabolic dysfunction-associated steatotic liver disease - Martínez-Sanz, Javier; Talavera-Rodríguez, Alba; Díaz-Álvarez, Jorge; Rosas Cancio-Suárez, Marta; Rodríguez, Juan Miguel; Alba, Claudio; Montes, María Luisa; Martín-Mateos, Rosa; Burgos-Santamaría, Diego; Moreno, Santiago; Serrano-Villar, Sergio; Sánchez-Conde, Matilde (Frontiers in Immunology, 2023)
homogeneity across individuals, in contrast to that observed in the HIV+NAFDL-group, in which the dispersion was higher (Permanova test, p value <0.001; ANOSIM, p value <0.001). MASLD but not HIV determined a different microbiota structure (HIV +MASLD-vs.HIV + MASLD + , q-value = 0.002; HIV -MASLD + vs. HIV + MASLD + , q-value = 0.930; and HIV - MASLD + vs. HIV + MASLD -, q-value < 0.001). The most abundant genera in MASLD-were Prevotella, Bacteroides, Dialister, Acidaminococcos, Alloprevotella, andCatenibacterium. In contrast, the most enriched genera in MASLD+ were Ruminococcus, Streptococcus, Holdemanella, Blautia, and Lactobacillus.We found a microbiome signature linked to MASLD, which had a greater influence on the overall structure of the gut microbiota than HIV status alone.